Galaxies in the central regions of simulated galaxy clusters - Ragagnin, Antonio; Meneghetti, Massimo; Bassini, Luigi; Ragone-Figueroa, Cinthia; Granato, Gian Luigi; Despali, Giulia; Giocoli, Carlo; Granata, Giovanni; Moscardini, Lauro; Bergamini, Pietro; Rasia, Elena; Valentini, Milena; et al. (Astronomy and astrophysics, 2022)
Context. Recent observations found that observed cluster member galaxies are more compact than their counterparts in ΛCDM hydrodynamic simulations, as indicated by the difference in their strong gravitational lensing properties, and they reported that measured and simulated galaxy-galaxy strong lensing events on small scales are discrepant by one order of magnitude. Among the possible explanations for this discrepancy, some studies suggest that simulations with better resolution and implementing different schemes for galaxy formation could produce simulations that are in better agreement with the observations. Aims. In this work, we aim to assess the impact of numerical resolution and of the implementation of energy input from AGN feedback models on the inner structure of cluster sub-haloes in hydrodynamic simulations. Methods. We compared several zoom-in re-simulations of a sub-sample of cluster-sized haloes obtained by varying mass resolution and softening the length and AGN energy feedback scheme. We studied the impact of these different setups on the sub-halo (SH) abundances, their radial distribution, their density and mass profiles, and the relation between the maximum circular velocity, which is a proxy for SH compactness Results. Regardless of the adopted numerical resolution and feedback model, SHs with masses of MSH ≲ 1011 h−1 M⊙, the most relevant mass range for galaxy-galaxy strong lensing, have maximum circular velocities ∼30% smaller than those measured from strong lensing observations. We also find that simulations with less effective AGN energy feedback produce massive SHs (MSH ≳ 1011 h−1 M⊙) with higher maximum circular velocity and that their Vmax − MSH relation approaches the observed one. However, the stellar-mass number count of these objects exceeds the one found in observations, and we find that the compactness of these simulated SHs is the result of an extremely over-efficient star formation in their cores, also leading to larger than observed SH stellar mass. Conclusions. Regardless of the resolution and galaxy formation model adopted, simulations are unable to simultaneously reproduce the observed stellar masses and compactness (or maximum circular velocities) of cluster galaxies. Thus, the discrepancy between theory and observations that emerged previous works. It remains an open question as to whether such a discrepancy reflects limitations of the current implementation of galaxy formation models or the ΛCDM paradigm.
Gesehen am 16.11.2022